Identifications of Barriers in Implementation of Digital Technology in Secondary schools of Punjab - Ghani, Sajida; Malik, Farah; Ullah, Shamim (Pakistan Journal of Humanities and Social Sciences, 2024)
The objective of this study was to discuss the benefits of digitization in Pakistani schools. After identifying barriers related with infrastructure, teacher and students, the aim of this study was to encourage students for the tackling of these barriers. As these barriers are main hindrances to get quality education. Quantitative approach was used in the study. Survey method was applied. The accessible population of the study was school teachers from various Public sector schools of Punjab, Pakistan. Convenience sampling technique was used to obtain sample of the study. The sample of the study was 300 school teachers. A questionnaire was developed for the collection of data. The validity of the questionnaire was obtained through expert opinion while reliability was obtained through cronbach alpha. The alpha value was .75. Descriptive statistical techniques were used for data analysis. The findings of the study were that key barriers in implementation of digital technology include inadequate infrastructure, limited access to technology, insufficient teacher training, resistance to change, concerns about privacy and security, and disparities in digital literacy among students. Furthermore, the research delves into the socio-economic, cultural, and policy-related factors that contribute to the complexity of these barriers. It also investigates potential strategies and solutions to overcome these obstacles, emphasizing the importance of collaborative efforts between stakeholders, policy-makers, educators, and technology developers. The findings of this study contribute to the ongoing discourse on technology in education and provide valuable insights for creating more inclusive, effective, and sustainable digital learning environments.